The effects of biogenic amines in Chinese Huangjiu on the behavior of mice and hangover headache‐related indices. Issue 12 (17th August 2022) - Zhao, Wenmei; Fu, Zukang; Wang, Xin; Mao, Qingzhong; Luan, Chunguang; Chen, Shanbin; Zhang, Fengjie; Yu, Jiajun; Yao, Yiping; Li, Yishu; Hao, Feike; Wang, Deliang; et al.
Abstract: Huangjiu (Chinese rice wine) is a popular and traditional alcoholic beverage in China; however, the consumption of Huangjiu readily results in hangover symptoms. The aim of this study was to identify the main components associated with behavioral inhibition, headache, and the relevant mechanisms by using a mice hangover model. The results of an open‐field experiment revealed that the key biogenic amine associated with mice behavior was histamine, which inhibited the behavior activity of mice in a dose‐dependent manner. Moreover, histamine treatment decreased the levels of serotonin (5‐HT) and 5‐hydroxyindole acetic acid. In addition, the levels of dopamine and nitric oxide, which are associated with migraine, increased in the brain tissue of mice. In addition, the expression of receptor genes of 5‐HT, including Htr1a, Htr1f, and Htr2c, is essential in regulating various behaviors and mental activities. In conclusion, the present study demonstrated that histamine is a key component in Huangjiu, and it is related to hangover symptoms by affecting the level of 5‐HT and its receptors. Abstract : At present, hangover‐induced dizziness, headache, and movement imbalance have been largely underexplored. This research sheds new light on BAs found in Huangjiu by using an alcohol consumption mice model. The behavioral indicators of mice were analyzed to find out which types of BAs could cause various hangover symptoms. In addition, the content of 5‐HT, 5‐HIAA, DA, and NO in brain tissue was also analyzed to explore the association between histamine and these substances. The key genes of the 5‐HT generation pathway were explored to reveal the mechanism of migraines. This work provides a foundation for improving the quality of Chinese Huangjiu.